PENGARUH BRAND IMAGE, BRAND EXPERIENCE DAN BRAND EQUITY TERHADAP MINAT BELI ULANG DENGAN BRAND PREFERENCE SEBAGAI VARIABEL MEDIASI DI KHAB KHUN AMBARAWA - Ajeng Hala Sekar Arum Sasi (Jurnal Akuntansi dan Pajak, 2023)
This study aims to examine the effect of brand image, brand experience, and brand equity on repeat purchase in Khab Khun Thai Tea Ambarawa with brand preference as a mediating variabel. The research problem is how to increasing selling repurchase intention in Khab Khun Thai Tea Ambarawa. The variable used in this study is brand image, brand experience, as variabel independen, brand perference as variable intervening and repeat purchase as variabel dependen. The sampling method used on this research is purposive sampling technique. Sample collected from 130 respondents of customer in Khab Khun Thai Tea Ambarawa. Technique of data collection conducted by survey through questionnaires. Data analysis was performed by descriptive analysis method and the method SEM. The result showed that customer on average make repurchase in Khab Khun Thai Tea Ambarawa more than twice. The result of data anlysis using the AMOS indicates that there is a positive and significant through brand image, brand expereince, and brand equity in the repeat purchase. Based on the research results, repeat purchase can be increased through brand preference. Keywords : brand image, brand experience, brand equity, repeat purchase, brand preference.